Experimental comparison of open sun drying and solar drying based on evacuated tube collector - Prashant Singh; Shubham Vyas; Avadhesh Yadav (International Journal of Sustainable Energy, 2019)
In this article, an experimental comparison between open sun and solar drying is done. The thermal performance of evacuated tube based solar dryer is investigated with drying characteristics of Phyllanthus Emblica (Anvla), Aloe Vera, Aegle Marmelos (Bel) and leaves of Azadirachta Indica (Neem), Aegle Marmelos (Bel) and Psidium Guajava (Guava). In this setup, an evacuated tube collector, shell and tube heat exchanger and drying chamber are used. It was found that the maximum temperature difference between hot air and ambient air is 35.4°C and maximum efficiency of the setup is calculated as 55%. The average drying rate of Phyllanthus Emblica (Anvla), Aloe Vera and Aegle Marmelos (Bel) is measured as 0.46 g/min, 0.44 g/min, and 0.39 g/min respectively which are higher than that of Open Sun Drying. The leaves of Azadirachta Indica (Neem), Aegle Marmelos (Bel) and Psidium Guajava (Guava) also get dried with faster rates of 0.18 g/min, 0.17 g/min, and 0.14 g/min respectively.